2014
DOI: 10.12954/pi.14067
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of multiparametric prostate magnetic resonance imaging in the detection of cancer distribution: histopathological correlation with prostatectomy specimens

Abstract: PurposeTo prevent overtreatment, it is very important to diagnose the precise distribution and characteristics of all cancer lesions, including small daughter tumors. The purpose of this study was to evaluate the efficacy of T2-weighted magnetic resonance imaging (T2W), diffusion-weighted magnetic resonance imaging (DWI), magnetic resonance spectroscopy (1H-MRS), and prostate biopsy (PBx) in the detection of intraprostatic cancer distribution.MethodsAll patients underwent T2W, DWI, 1H-MRS, and PBx followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our results are different from those of Kitamura et al who found lower sensitivity rates for DWI (51%) and a higher specificity (89%). However, their results were also influenced by the quantitative interpretation (ADC) and the ADC maps [4]. Concerning the ADC values, our results are in accordance with those obtained by deCobelli et al who also demonstrated a stratified decrease in ADC values in accordance to the increase in Gleason scoring for malignant lesions [9].…”
Section: Diagnostic Efficiencysupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are different from those of Kitamura et al who found lower sensitivity rates for DWI (51%) and a higher specificity (89%). However, their results were also influenced by the quantitative interpretation (ADC) and the ADC maps [4]. Concerning the ADC values, our results are in accordance with those obtained by deCobelli et al who also demonstrated a stratified decrease in ADC values in accordance to the increase in Gleason scoring for malignant lesions [9].…”
Section: Diagnostic Efficiencysupporting
confidence: 92%
“…We analyzed the data using the EpiInfo v 7.1.4.0 (Centers for Disease Control and Prevention, Atlanta, USA) and the IBM-SPSS V19.0 demo (SPSS Inc, an IBM company) software. After dichotomization of the initial PI-RADS classification as benign (1, 2) and malignant (3,4,5), clinical efficiency indicators (sensitivity, specificity, positive and negative likelihood ratio) were calculated for qualitative DWI, referring to the gold standard. ADC values were analyzed according to the final diagnosis.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Belgium, Japan, Finland, Austria, United States, Brazil, Italy, Spain and Turkey respectively. Among them 15 were (8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) prospective studies and 30 were retrospective studies. The publication period of these studies was from 2005 to 2018.…”
Section: Study Selectionmentioning
confidence: 99%
“…In terms of comparing preoperative mp-MRI with postoperative histopathology, Styles et al [ 23 ] from Melbourne demonstrated (n=38) that analyzing T2WI and DWI in combination was the best strategy for detecting localized PC with a reported sensitivity of 85% for cancers with a volume >0.5 mL. Kitamura et al [ 24 ] (n=54) examined cancer distribution in men who underwent mp-MRI of the prostate (T2, DWI, MRS) and prostate biopsy followed by radical prostatectomy. The prostate was divided into 12 segments, each of which was examined for malignancy on the basis of T2WI, DWI, and MRS.…”
Section: Comparison Of Preoperative Mp-mri With Radical Prostatectomymentioning
confidence: 99%